Implementation of The Kampus Mengajar Policy Program in Enhancing Literacy, Numeracy, and Technology Adaptation - Subagdja, R Oetje; Qotrunada, Rasya; Pratidina, Ginung (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
The aim of this research is to understand how the Kampus Mengajar program enhances literacy, numeracy, and technology adaptation in Ciderum Village, Caringin District. The policy implementation theory used in this research is the Implementation Policy theory by George Edward III, which includes four dimensions: Communication, Resources, Disposition, and Bureaucratic Structure. The research applies a qualitative descriptive research method, relying on information gathered through observation, interviews, and documentation. The analysis techniques include data summarization, presentation, and drawing conclusions. The results indicate that the implementation of the Kampus Mengajar program in literacy, numeracy, and technology adaptation learning can be considered good. The school has implemented literacy, numeracy, and technology adaptation learning and collaborated with teachers and parents in the learning process for each student. Although the implementation at SDN Cikereteg 03 is not yet optimal and maximal, the school continuously strives to ensure that it can be implemented optimally and maximally for all students.